2016
DOI: 10.3390/nu8070426
|View full text |Cite
|
Sign up to set email alerts
|

Lutein, Zeaxanthin and Meso-zeaxanthin Supplementation Associated with Macular Pigment Optical Density

Abstract: The purpose of this study was to evaluate the effects of lutein, zeaxanthin and meso-zeaxanthin on macular pigment optical density (MPOD) in randomized controlled trials (RCTs) among patients with age-related macular degeneration (AMD) and healthy subjects. Medline, Embase, Web of Science and Cochrane Library databases was searched through May 2016. Meta-analysis was conducted to obtain adjusted weighted mean differences (WMD) for intervention-versus-placebo group about the change of MPOD between baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 62 publications
5
74
0
4
Order By: Relevance
“…It should be noted that tuna fish, especially tinned tuna, is an important source of meso-zeaxanthin. Meso-zeaxanthin supplementation has been shown to improve macular pigment optical density in both AMD patients and healthy subjects in a dose-response relationship [43]. In the Meso-zeaxanthin Ocular Supplementation Trial (MOST), it was found that a significant increase in macular pigment from baseline was observed in the meso-zeaxanthin treated group [44].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that tuna fish, especially tinned tuna, is an important source of meso-zeaxanthin. Meso-zeaxanthin supplementation has been shown to improve macular pigment optical density in both AMD patients and healthy subjects in a dose-response relationship [43]. In the Meso-zeaxanthin Ocular Supplementation Trial (MOST), it was found that a significant increase in macular pigment from baseline was observed in the meso-zeaxanthin treated group [44].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that MP levels in the retina can be augmented through increased intake of dietary L and Z in healthy and diseased retinas, suggesting the possibility that therapeutic intervention in the form of dietary modification or nutritional supplementation may modulate the risk of diseases associated with a relative lack of MP 49 50. Furthermore, inclusion of MZ in the carotenoid supplementation results in greater increase in MP compared with supplements lacking this central carotenoid 51 52…”
Section: Lutein and Zeaxanthinmentioning
confidence: 99%
“…Lutein and zeaxanthin are xanthophyll carotenoids that are concentrated in the macula and are known for their roles in antioxidation [19][20][21]. One systemic review with meta-analysis of twenty randomized controlled trials (RCTs) revealed a proportional increase of macular pigment optical density with lutein and zeaxanthin supplementation [22], indicating beneficial efficacy of supplemented lutein and zeaxanthin intake in improving ocular health. Accumulating evidence has shown that black currant (Ribes nigrum L.) is beneficial for visual functions potentially by increasing ocular blood flows to mitigate eye fatigue symptoms [23,24].…”
Section: Introductionmentioning
confidence: 99%